The use of online discussion forum among undergraduates of distance education programme / Normah Hj. Hussain - Hj. Hussain, Normah (2007)
This study is designed to discover the use of online discussion forum among undergraduates of distance education programme. In the distance learning environment,the online discussion forum is used as a medium for communication. Therefore the aims of this study are to highlight the strengths and weaknesses of using online discussion forum, to provide the suggestions as to improve the weaknesses and finally to investigate the respondents opinions towards the implementation of online discussion forum in schools.For the purpose of this study two instruments have been designed for data collection. A close ended questionnaire comprised of 30 items and three open ended questionnaire were administered to a group of 58 OUM (Open University Malaysia) Final Year TESL (Teaching English as a Second Language) undergraduates. The second instrument used is a focus group interview with three structured questions. A group of 8 undergraduates involved in the group interview. Percentage was used in analyzing the data and the findings were written descriptively. From the analysis of findings it was found that the undergraduates view positively towards the use of online discussion forum and it has contributed to more strengths than weaknesses. The most strength is mainly on the sharing of information; communicate ideas, learnt from others' point of views and opportunity for contributing ideas. The weaknesses found were the server problems which build the gap between rural and urban participation in the online discussion. A well planned online discussion forum and immediate action is needed to overcome the problems so that everybody particularly undergraduates of distance education will have less problems to communicate anywhere and any place in the country. A positive response towards the implementation of online discussion forum in school has also been positively highlighted.